Power struggles in the German Christian Democrats. The dynamics of three consecutive leadership contests - Jun, Uwe; Minas, Marius (Frontiers in Political Science, 2023)
In 2021, the German Christian Democrats held three leadership contests. First, the Christian Democratic Union (CDU) had to find a new party leader. While the members tended toward the more conservative candidate, Friedrich Merz, the party elite increasingly spoke out in favor of the more moderate Armin Laschet, who prevailed at a digital party conference. Just a few months later, he was challenged by his counterpart in the CDU's Bavarian sister party (CSU), Markus Söder, over who would be the joint chancellor candidate in the upcoming federal election. Söder was clearly favored by voters as well as the party on the ground, but Laschet found powerful and decisive support in the CDU's party elite. Yet the Christian Democrats surprisingly lost the federal election, mainly because of the unpopularity of its frontrunner. After Laschet announced his retirement, the party prepared the third leadership contest. This time, the party headquarter declared a membership ballot as the mode of decision-making, in which Merz triumphed. As this study clearly points out, each of the three selection modes developed its own dynamic in the matter of influencing factors, qualitatively as well as quantitatively. Process-tracing shows that the various selection processes are interrelated in terms of their dynamics and decision modes.